Fabrication of ZrO2-Bearing lithium-silicate glass-ceramics by pressureless sintering and spark plasma sintering - Ghayebloo, M. (2020)
Objective: the present study evaluated the effect of the Spark Plasma Sintering (SPS) and Pressureless Sintering (PLS) methods on the physical and mechanical properties of ZrO2-bearing Lithium Silicate (ZLS) glass-ceramics. Method: SPS and PLS methods were used for fabricating of the zirconia-bearing Lithium Silicate glass-ceramics. Several sintering temperatures were applied in order to achieving the best mechanical and physical properties in both methods. For this purpose, the particle size measurement of the glass powder was performed. Field Emission Scanning Electron Microscope (FESEM) was carried out for evaluation of the microstructure. X-ray diffraction (XRD) was used to investigate the amorphous or crystalline state of the samples. Fourier Transform Infrared Spectroscopy (FTIR) was used for the investigation of the chemical bonds. Flexural strength, Vickers microhardness, fracture toughness, and physical properties such as bulk density, water absorption, and the apparent porosity of the samples were measured. Results: It is possible to fabricate ZLS glass-ceramics by the SPS method at a sintering temperature approximately 350 °C lower than the sintering temperature of the PLS method. Results of the SPS showed SGC, 550 °C (SPS Glass Ceramic sintered at 550 °C) had the highest flexural strength (255.10 ± 15.44 MPa), fracture toughness (3.15 ± 0.62 MPam1/2), Vickers microhardness (7.96 ± 0.13 GPa) and bulk density (2.63 ± 0.02 g/cm3); the lowest water absorption (0.11 ± 0.12) and, apparent porosity (0.25 ± 0.32). Results of the PLS showed PLGC, 900 °C (PLS Glass Ceramic sintered at 900 °C) had the flexural strength (160.27 ± 12.69 MPa), the highest Vickers microhardness (7.22 ± 0.67 GPa) and bulk density (2.53 ± 0.03 g/cm3); the lowest water absorption (0.15 ± 0.21) and, apparent porosity (0.39 ± 0.54). According to the XRD patterns and FESEM images, SGC, 550 °C has Li2Si2O5 spherical nanocrystals (approximately 50–100 nm diameters). Significance: Different sintering temperatures in the SPS and PLS methods have an obvious effect on the microstructure, mechanical, and physical properties of ZrO2-bearing Lithium Silicate (ZLS) glass-ceramics. Sintering temperature was decreased in SPS compared to the PLS method and nanocrystals of Li2Si2O5 formed.